ДРЕВНИЕ ПОСЕЛЕНИЯ ОРДУБАДА. - Алиев, Э. Г. (Journal of Oriental Studies, 2016)
Нахчыван Автономды Республикасының шығыс жағы әртүрлі тарихи кезеңдердің пайдалы археология- лық ескерткіштеріне бай. Әсіресе Гиланчай, Ванандчай және Ордубадчай өзендерінің бастауында орналасқан ежелгі тұрғындар зерттеушілер назарын көптеп ау- даруда. Автор бұл мақалада Ордубадтың ежелгі тұр- ғындары жайында тоқталады. The Eastern part of Nakhchivan AR, situated between Zangazur and Karadagh ridges of Lesser Caucasus is rich of the archeological monuments of different historical periods. The monuments especially are placed densely on the valley of Gilanchay,the 2nd biggest river of Nakhchivan. Here had been found and partly investigated the living places and necropolises,such as Plovdagh, Khali-Keshan, Mardangol, Munduklutepe, Damyalar and Kumluk.